1997
DOI: 10.1038/bjc.1997.541
|View full text |Cite
|
Sign up to set email alerts
|

The risk profile of childhood leukaemia in Greece: a nationwide case-control study

Abstract: Summary The risk profile of childhood leukaemia in Greece was studied through a case-control investigation that included all 153 incident cases of the disease, ascertained throughout the country during 1993 and 1994, and two hospital controls for every case matched for gender, age and place of residence. The data were analysed using conditional logistic regression and the associations are expressed in terms of adjusted odds ratios (OR) and their 95% confidence intervals. Cases were born to mothers of a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
142
6
14

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(176 citation statements)
references
References 49 publications
13
142
6
14
Order By: Relevance
“…This was apparently not an effect of macrosomia at birth. An increased risk of childhood cancer with high birth weight has been reported (Daling et al, 1984;Greenberg et al, 1985;Kaye et al, 1991;Petridou et al, 1997) and was also present in our material, though stratification for birth weight did not remove the statistically significant increase in OR. The observed increased risk at low birth weight was also found by Forsberg and Källén (1990).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This was apparently not an effect of macrosomia at birth. An increased risk of childhood cancer with high birth weight has been reported (Daling et al, 1984;Greenberg et al, 1985;Kaye et al, 1991;Petridou et al, 1997) and was also present in our material, though stratification for birth weight did not remove the statistically significant increase in OR. The observed increased risk at low birth weight was also found by Forsberg and Källén (1990).…”
Section: Discussionsupporting
confidence: 73%
“…A Danish study (Mellemkjaer et al, 2000) revealed a moderately increased risk for childhood lymphomas and leukaemia of borderline statistical significance, while a positive association between childhood leukaemia and maternal diabetes was reported from Greece (Petridou et al, 1997).…”
mentioning
confidence: 97%
“…To date, 13 case -control studies (Davis et al, 1988;Magnani et al, 1988;van Duijn et al, 1988;Shu et al, 1995;Petridou et al, 1997;Dockerty et al, 1999;McKinney et al, 1999;Schüz et al, 1999;Rosenbaum et al, 2000;Hardell and Dreifaldt, 2001; UK Childhood Cancer Study Investigators, 2001;Lancashire and Sorahan, 2003;Jourdan-Da Silva et al, 2004) have reported no association between breastfeeding and overall childhood leukaemia or ALL risk. Two of these previous studies restricted their analysis to children diagnosed between age 2 and 5 years and found no significant effect of breastfeeding on risk of leukaemia (Shu et al, 1995;UK Childhood Cancer Study Investigators, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The results from the UKCCS study with respect to breastfeeding were compared with relevant results from other epidemiological studies of childhood cancer (van Steensel-Moll et al, 1986;McKinney et al, 1987;Davis et al, 1988;Hartley et al, 1988;Magnani et al, 1988;Golding et al, 1990;Shu et al, 1995;Petridou et al, 1997;Grufferman et al, 1998;Dockerty et al, 1999;Schüz et al, 1999;Shu et al, 1999;Smulevich et al, 1999;Infante-Rivard et al, 2000;Rosenbaum et al, 2000;Bener et al, 2001;Hardell and Dreifaldt, 2001). The UKCCS results did not differ significantly from those of previous studies, they have been combined with these and the overall results are shown for leukaemia (Figure 1), Hodgkin's disease (Figure 2), non-Hodgkin's lymphoma (Figure 3), other childhood cancers (Figure 4) and all childhood cancers combined ( Figure 5).…”
Section: Acute Myeloidmentioning
confidence: 99%
“…Several case-control studies of children with leukaemia have reported a significantly reduced risk associated with having been breastfed as infants (Shu et al, 1999;Smulevich et al, 1999;Infante-Rivard et al, 2000;Bener et al, 2001), although not all studies have noted such a relationship (van Steensel-Moll et al, 1986;McKinney et al, 1987;Davis et al, 1988;Magnani et al, 1988;Shu et al, 1995;Petridou et al, 1997;Dockerty et al, 1999;Schüz et al, 1999;Rosenbaum et al, 2000;Hardell and Dreifaldt, 2001). Others have reported a significantly reduced risk of Hodgkin's disease (Grufferman et al, 1998) and non-Hodgkin's lymphoma (Bener et al, 2001) in breastfed children.…”
mentioning
confidence: 99%